EMPOWERING RURAL COMMUNITIES THROUGH SALAK FRUIT INNOVATION: APPLYING THE BUSINESS MODEL CANVAS FOR SUSTAINABLE ENTREPRENEURSHIP - Lindiawati, L; Yulianti, Emma; Nurmianto, Eko; Indasah, Alfiah; Buana, Calvina Angelia Diwangkari; Yosephina, Grace (Erudio Journal of Educational Innovation, 2025)
This community engagement project aimed to strengthen rural entrepreneurship through the innovation of salak fruit processing combined with Business Model Canvas (BMC) training. Local farmers were encouraged to diversify salak into various processed products such as chips, dodol, and juices to increase product value and market competitiveness. The BMC framework was introduced as a practical tool to help participants analyze value propositions, customer segments, revenue streams, and cost structures. Through participatory workshops, farmers gained hands-on experience in developing business models that were both feasible and sustainable. The results showed significant learning improvement, with participants’ average pre-test score at 46 and post-test score rising to 81. This demonstrated enhanced understanding of entrepreneurial concepts and the practical application of BMC. Moreover, product diversification not only improved farmers’ confidence in entrepreneurship but also opened new market opportunities beyond traditional raw fruit sales. The integration of product innovation with entrepreneurial training fostered community capacity building and strengthened economic resilience. This initiative demonstrates how higher education institutions can bridge academic knowledge with community needs, creating sustainable local economic development through agro-based innovation.